2011
DOI: 10.1021/bm201198x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Injectable Hyaluronic Acid Hydrogel Degradation Behavior on Infarction-Induced Ventricular Remodeling

Abstract: Increased myocardial wall stress after myocardial infarction (MI) initiates the process of adverse left ventricular (LV) remodeling that is manifest as progressive LV dilatation, loss of global contractile function, and symptomatic heart failure, and recent work has shown that reduction in wall stress through injectable bulking agents attenuates these outcomes. In this study, hyaluronic acid (HA) was functionalized to exhibit controlled and tunable mechanics and degradation once crosslinked, in an attempt to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
119
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(128 citation statements)
references
References 66 publications
8
119
1
Order By: Relevance
“…CreERT2/+ Yap fl/fl Taz fl/fl R26 Tomato/+ mice using an HA polymer modified by hydroxyethyl methacrylate (HEMA-HA, 20% modification) to render it photopolymerizable and hydrolytically degradable (64). Hydrogel precursor solutions (25 μl per animal) consisted of HEMA-HA (6.0% weight) dissolved in a photoinitiator solution, as previously described (47), and contained either 1 μg recombinant IFN-γ (485-MI/ CF; R&D Systems) or no drug.…”
Section: Methodsmentioning
confidence: 99%
“…CreERT2/+ Yap fl/fl Taz fl/fl R26 Tomato/+ mice using an HA polymer modified by hydroxyethyl methacrylate (HEMA-HA, 20% modification) to render it photopolymerizable and hydrolytically degradable (64). Hydrogel precursor solutions (25 μl per animal) consisted of HEMA-HA (6.0% weight) dissolved in a photoinitiator solution, as previously described (47), and contained either 1 μg recombinant IFN-γ (485-MI/ CF; R&D Systems) or no drug.…”
Section: Methodsmentioning
confidence: 99%
“…Although the basis for infarct expansion is likely to be multifactorial, local mechanical signals, such as increased stress and strain within the MI and border zones, likely promulgate this process. The injection of biomaterials within the MI region have been clearly shown to favorably alter these biomechanical factors and reduce adverse post-MI remodeling, and as such, translational studies regarding the underlying mechanisms and pathways by which these materials are operative have accelerated (Landa et al, 2008;Mukherjee et al, 2008;Pilla et al, 2009;Ifkovits et al, 2010;Morita et al, 2011;Rane et al, 2011;Tous et al, 2011Tous et al, , 2012Burdick et al, 2013;Johnson and Christman, 2013;Shuman et al, 2013). Using myocardial injections of a hyaluronic acid and poly (lactide-co-glycolide)-based microsphere (∼50 mm) formulation, it has been previously demonstrated that changing the degradation rates of the microsphere formulation (hydroxyethyl methacrylate) or the microsphere concentration (0-300 mg/ml) can be achieved, which in turn can alter tissue mechanical properties (Ifkovits et al, 2010;Tous et al, 2011Tous et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…These cell types, the macrophage and fibroblast, play a critical role in the post-MI remodeling process (Lindsey et al, 2001;Ertl and Frantz, 2005;Hohensinner et al, 2010;Frangogiannis, 2012;Freytes et al, 2013;Goldsmith et al, 2013). Past studies have provided functional evidence that the effects of injected acellular biomaterials, such as CHAM upon LV geometry and post-MI remodeling, are not entirely due to the biophysical effects of the material itself but rather to the localized cellular response evoked by these biomaterials (Ifkovits et al, 2010;Rane et al, 2011;Tous et al, 2011Tous et al, , 2012Burdick et al, 2013;Shuman et al, 2013). Therefore, understanding how macrophage and fibroblast form and function within the MI region are affected following targeted CHAM injections remains a critical issue if these biomaterials are to continue advancement as a possible therapeutic for post-MI remodeling.…”
Section: Methodsmentioning
confidence: 99%
“…(49,54) Similar results were found in studies by the Burdick group aimed at investigating the relative influence of mechanical properties using degradable and non-degradable hyaluronic acid based gels of low and high storage moduli (approximately 8 kPa and 40 kPa respectively). (55,56) In the acute infarct ovine studies, significant decreases in ejection fraction (EF) from baseline was seen in all groups, including control. (55,56) However, despite the decrease in EF, cardiac output (stroke volume) was only shown to be significantly lower in the control group, while increased infarct thickness and reduced infarct size was seen in both treatment groups.…”
Section: Current Exploration Of Acellular Hydrogel Mechanisms Of Actionmentioning
confidence: 99%
“…(55,56) In the acute infarct ovine studies, significant decreases in ejection fraction (EF) from baseline was seen in all groups, including control. (55,56) However, despite the decrease in EF, cardiac output (stroke volume) was only shown to be significantly lower in the control group, while increased infarct thickness and reduced infarct size was seen in both treatment groups.…”
Section: Current Exploration Of Acellular Hydrogel Mechanisms Of Actionmentioning
confidence: 99%